Healing of severe polystructural limb wounds using vacuum therapy - Naumenko, Leonid; Horehliad, Olexii; Mametyev, Andriy; Kostrytsya, Konstantyn; Domansky, Andriy (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2017)
Vacuum-assisted wound closure has been known for the last two decades as an economically viable and effective treatment method, but the variety of patient injuries caused by severe polystructural (including combat) injuries requires further research into the effect of negative pressure on wound healing. Objective: to study the possibilities of vacuum-assisted wound closure therapy for the early management of patients with severe open polystructural injuries of limbs with fragmentation or gunshot character in comparison with conventional therapy. Methods: the results of treatment of 34 patients (men, mean age (30 ± 6) years) with open severe musculoskeletal injuries of the lower and upper extremities, which are accompanied by problems of primary closure of the wound, are analyzed. Before the application of vacuum-assisted wound closure therapy or traditional treatment, all patients had wound sanation and fasciotomy. Eighteen patients were included in the study group who underwent variable negative pressure. Standard wound treatment with antiseptics and the imposition of gauze dressings were applied in 16 affected control group. The condition of the wound was checked on the third and seventh day of treatment. The rate of healing was determined, which was determined by the difference between the initial areas and the areas identified during the study stage. Results: a significant decrease in the average wound area with Vacuum-assisted wound closure therapy (1.6 cm2 after 3 days, 3.9 cm2 after 7 hours) was recorded in comparison with the traditional method (0.8 and 3 cm2, respectively). Conclusions: a significant increase in the rate of initial healing of complex fragmentation and gunshot wounds in patients with vacuum-assisted wound closure therapy compared with traditional treatment in a control group was demonstrated. Primary application of vacuum-assisted wound closure therapy is most effective in the period corresponding to the second phase of the wound healing (3–7 days).